KOMPONEN LATIHAN FISIK TERHADAP RESIKO JATUH PADA LANSIA: SYSTEMATIC REVIEW - Alviana, Fifi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
To provide accurate and best information about the component of physical exercise against the risk of falling in the elderly. Researchers searched one electronic databases for relevant articles published between 2012 and 2017. Data were collected using inclusion and exclusion criteria. The Joanna Briggs Institute Instrument was used to evaluate the quality of the identified articles. The results obtained are 5 articles analyzed in a systematic review. The movement in physical exercise consists of heating, hearing movement. Physical exercises can be applied in communities, hospitals, nursing homes and home care. The appropriate component of physical exercise can prevent falls in the elderly. Keywords: elderly, risk of falls, component of physical exercise